The Impact of Resilience in The Psychosocial Support of Internally Displaced Secondary School Students in Cameroon - Cliford Fru-Ngongban Akenji (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2023)
This study sets out to determine the impact of resilience in the psychosocial support of internally displaced secondary school students in Cameroon. The researcher was motivated by the crises that is affecting two regions in the country which has exposed children to significant risks of diverse forms such as sexual violence, seizure of daily activities, dropping out of school, destruction of infrastructure, association to armed groups, family separation all resulting to extended psychosocial distress and mental disorders especially among some children.The mixed method approach was adopted by the researcher. In the quantitative phase, a sample of 317 participants was drawn from some public schools in the selected regions. The qualitative data was collected from the field with the aid of an Interview guide. Data were analysed used analysing using both descriptive and inferential statistics and the interview guide was analysed using the process of thematic content analysis. The results reveal that the impact of resilience in the psychosocial support of internally displaced secondary students in Cameroon was significant for all the predictive components thus indicating their significance in providing psychosocial assistance among internally displaced secondary school students